Occasional deconstructions - Wolfreys, Julian, 1958- (State University of New York Press, 2004)
"In Occasional Deconstructions, Julian Wolfreys challenges the notion that deconstruction is a critical methodology, offering instead a number of reintroductions or reorientations to the texts of Jacques Derrida and the idea or possibility of deconstructions. Proceeding from specific readings of various texts (both film and literary), as well as mobilizing a number of issues from Derrida's recent work surrounding questions of ethics, politics, and identity, Wolfreys considers the role of deconstruction in broader academic and institutional contexts, and questions whether, in fact, deconstruction can be called upon to function as theory at all."--Jacket